1998
DOI: 10.1089/aid.1998.14.1007
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Protease Inhibitors Fail to Inhibit HTLV-I Gag Processing in Infected Cells

Abstract: Protease inhibitors are currently the most effective antiviral agents against human immunodeficiency virus type 1 (HIV-1). In this study we determined the effect of four HIV-1 protease inhibitors on human T cell leukemia virus type 1 (HTLV-I). Rhesus monkey cells infected with HTLV-I were treated with different concentrations of indinavir, saquinavir, ritonavir, or nelfinavir. The effect of these inhibitors was monitored through their effect on the processing efficiency of the viral Gag protein in cells, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Only compound 3 inhibited the PR up to 10 M (5). Four of the HIV-1 PR inhibitors used in clinical practice were also tested on HTLV-1 Gag processing in vitro and did not show any effect (50). These results demonstrate the large differences in specificity of the two enzymes.…”
Section: Mutations Affecting the S3/s1-binding Sites Of Htlv-1 Protease-mentioning
confidence: 88%
“…Only compound 3 inhibited the PR up to 10 M (5). Four of the HIV-1 PR inhibitors used in clinical practice were also tested on HTLV-1 Gag processing in vitro and did not show any effect (50). These results demonstrate the large differences in specificity of the two enzymes.…”
Section: Mutations Affecting the S3/s1-binding Sites Of Htlv-1 Protease-mentioning
confidence: 88%
“…Retroviral NCs perform a variety of essential functions throughout the viral life cycle, and there are many differences between HIV-1 and HTLV-1 that may explain why the CTD is retained in one case but not in the other (77)(78)(79)(80)(81). In addition, the viruses appear to have evolved different mechanisms to resist cellular restriction factors such as human APOBEC3G.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, at least two studies have shown that a nucleoside analogue, such as lamivudine, known for its ability to control HIV infection, was not as effective toward HTLV-1 infection in vitro, probably due to some natural resistance (12,40). Similarly, none of the inhibitors designed to act against the HIV-1 proteinases was able to efficiently inhibit Gag processing in HTLV-1-infected cells (31).…”
Section: Discussionmentioning
confidence: 99%